Spider webs capture environmental DNA from terrestrial vertebrates - Newton, Joshua; Nevill, Paul; Bateman, Phillip; Campbell, Mathew; Allentoft, Morten (Cell Press, 2024)
Environmental DNA holds significant promise as a non-invasive tool for tracking terrestrial biodiversity. However, in non-homogenous terrestrial environments, the continual exploration of new substrates is crucial. Here we test the hypothesis that spider webs can act as passive biofilters, capturing eDNA from vertebrates present in the local environment. Using a metabarcoding approach, we detected verte brate eDNA from all analyzed spider webs (N = 49). Spider webs obtained from an Australian woodland locality yielded vertebrate eDNA from 32 different species, including native mammals and birds. In contrast, webs from Perth Zoo, less than 50 km away, yielded eDNA from 61 different vertebrates and produced a highly distinct species composition, largely reflecting exotic species hosted in the zoo. We show that higher animal biomass and proximity to animal enclosures increased eDNA detection probabil ity in the zoo. Our results indicate a tremendous potential for using spider webs as a cost-effective means to monitor terrestrial vertebrates.